Nainā-jogina . - Jha, Rajeshwar, 1925- (Maithilī Sāhitya Saṃsthāna, 1973)
On nainā-jogina, an esoteric ritual ceremony of Mithila performed at the time of marriage to imporve conjugal relations; in Maithili, dialect of Hindi.